A Guide for Training Organizations to Promote Veteran‐Friendly Practices. Issue 166 (30th September 2020) - Kirchner, Michael J.; Minnis, Sarah E.; Stull, Faith
Abstract: While few organizations would willingly identify as being unfriendly to veterans, articulating what being veteran friendly means is an ongoing challenge. As such, organization leaders may struggle to explain the term, beyond reporting a need to support military veterans. This knowledge gap could contribute toward the high turnover rates of military veterans, particularly within their first 2 years of employment. To lessen these struggles, the authors propose a framework focused on building and sustaining a veteran‐friendly organization. The framework provides an opportunity for organization leaders to improve their knowledge and preparation for creating a lasting veteran‐friendly culture. The paper introduces veteran employment challenges, offers a review of literature on veteran‐friendly organizations, details the proposed framework on veteran‐friendly practices, and concludes with a reflection on the framework and implications for organizations and scholars interested in supporting veteran career transitions.